One way to evaluate the impact of scientific research - Dávalos-Sotelo, Raymundo (Instituto de Ecología, A.C., 2015)
The internationally most widely used criterion to evaluate scientific journals is based on the value of the impact Factor (FI) generated from the Journal Citation Reports (JCR) database published annually on the Web of Science platform from Thomson Reuters. The central argument of this article is that the most complete form of evaluation of the work of scientists through metrics of easy access and general scope as the index h of Hirsch from the database of Google Scholar, plus some other considerations. The author recognizes that if the goal to achieve is to measure the impact of purely academic research, the JCR impact Factor (FI) is the most appropriate means, but if the objective is to measure the impact of research in the real world, then other metrics and assessment criteria should be used. Here it is suggested that the true relevance of the publications is reflected in a more natural way among a heterogeneous user audience with the information included in the Google Scholar platform. For developing countries, the paper highlights that it is more important to define their policies of support for research than to seek greater international visibility or global relevance of their journals. It has been shown here that the message is the important subject matter and not the means of publication. Nevertheless, scientific journals do deserve indeed the greatest attention by the responsible authorities of the sciences in developing countries.